Extracting Power from Libya's Great Man-Made River using Python, Lucid Turbine, and Hydro XS - Abubaker Ali Mohamed Abudabbous (المجلة الأفروآسيوية للبحث العلمي, 2025)
This paper investigates the potential for sustainable energy generation within Libya's Great Man-Made River (GMMR) Project through the integration of in-pipe hydrokinetic turbines, specifically focusing on a comparative analysis of Lucid Energy's LucidPipe Power System and Hydro XS Turbines. The GMMR, a monumental civil engineering endeavor, transports vast quantities of water across Libya, presenting a unique opportunity for harnessing untapped energy from its extensive pipeline network. Utilizing Python-based simulation, this study models the energy recovery potential by integrating these turbines within the GMMR infrastructure. For the LucidPipe system, a conical nozzle is incorporated to regulate and increase velocity or pressure, while the Hydro XS Turbines are evaluated for direct integration. The simulation incorporates fluid dynamics principles, including head loss calculations due to friction and minor losses, and evaluates electrical power output under a specified GMMR pipe water velocity of 0.95 m/s and realistic pressure assumptions derived from GMMR operational data. The findings demonstrate significant energy generation capabilities for both technologies, highlighting their feasibility and environmental benefits in augmenting Libya's energy supply while maintaining the primary function of water delivery. This research provides a foundational analysis for future detailed engineering and economic assessments of such systems within the GMMR infrastructure.